A production systems study on Dyson Surface Coating Corporation - Marcelo, Juan Carlos B.; Banquillo, Elna A.; Rubite, Annicel P. (Diliman, Quezon City College of Engineering, 1996)
In a country working towards industrialization, like the Philippines, companies strive to achieve effectivity and efficiency in their production systems. In order to attain this goal, a complete understanding of the system is necessary in order to identify the flaws and constrains so as to plan appropriate courses of action. This involves the application of production/operations management through the combined efforts of management and administration, workers, and industrial engineers. Dyson Surface Coating Corporation is a service company involved in powder coating of metal items . At present, the company's performance was viewed as suboptimal by the proponents of the study. This was based on the study made which revealed a prolonged cycle time of operation, the absence of a forecasting system, and the absence of a production plan which were identified as the major problems of the system. After all the exhaustive analyses, the proponents of the study recommended the use of forecasting, the purchase of an electric hoist, and the development of a production plan (i.e. add a derusting line and increase the working hours at the powder coating conveyor system) to enhance productivity, thereby, improving profitability of the company.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Dyson Surface Coating Corporation; Manufacturing industry; Production engineering